Faculty Senate, Minutes and Resolution, October 16, 2014 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2014)
Valdosta State University. Faculty Senate, Minutes, October 16, 2014. Michael Noll; James Archibald; Linda Jurczak; Peggy Moch; Valdosta State University. Faculty Senate, Resolution on Sexual Harassment, October 16, 2014.
2 electronic documents. faculty-senate_20141016_minutes.pdf: 17 pages. 2755162 byte. faculty-senate_20141016_resolution.pdf: 1 pages. 132669 bytes.
Keywords: Faculty Senate (Valdosta State University); Minutes (Records); Electronic records; Sexual harassment